Heat flux performance of heterogeneous nanofluid boundary layer flows over an inclined cylinder using variant graphene and carbon-based nanoparticles / Siti Nur Ainsyah Ghani - Siti Nur Ainsyah , Ghani (2021)
The heat transfer processes, boundary layer, heat exchangers, nanofluid models are briefly explained in the initial part of study. Then, the laconic preface on magnetohydrodynamic (MHD) and stagnation point flow are also included. The equations of boundary layer assumptions for continuity, momentum and energy are describe generally followed by the selected cylindrical coordinates. The governing partial differential equations (PDEs) are molded according to Tiwari-Das model and reformulated into nonlinear ordinary differential equations (ODEs) by using similarity expressions. A shooting technique is opted to reformulate the ensuing equations into boundary value problems which are then solved numerically by using a finite difference code that executes the three-stage Lobatto IIIa formula in Matlab. Thus, variant graphene-based nanoparticles; graphenes, graphene nanoplatelets (GNPs), graphene oxides (GOs), Single Walled Carbon Nanotubes (SWCNTs) and Multiple Walled Carbon Nanotubes (MWCNTs) in a water-base fluid is the center of interest for the present study. The comparisons between the present and previous published results are presented for accuracy and veracity of the numerical results. The effects of constructive parameters toward the model on dimensionless velocity and temperature disseminations, reduced skin friction coefficient and reduced Nusselt number are presented graphically and discussed in details. Research outcomes show graphenes-water nanofluid has the highest heat flux performance compared to other selected nanofluids across many emerging parameters considered in this study.